EFFECTS ON MODIFIED PROPERTIES OF EXPANSIVE CLAY SOIL USING WASTE HOLLOW CONCRETE BLOCK (HCB) AND CEMENT PLASTER WASTE MATERIALS FOR SUBGRADE CONSTRUCTION - Chala, Galeta; Quezon, Emer Tucay; Mekonnen, Eyob; Ararsa, Woyesa (International Journal of Research -GRANTHAALAYAH, 2020)
Expansive soils characterized by changing its volume and strength due to seasonal variations. Due to this volume changes, expansive clay soil caused many problems in road construction and is relatively common in Ethiopia. As a result, such types of soil are not adequately for road construction, which requires proper attention. The focus of this study was to improve the engineering properties of the expansive clay soil with the addition of waste materials to use as a subgrade construction material. Soil samples were taken from three locations within the study area and performed laboratory tests for the moisture content, specific gravity, free swelling, Atterberg limit, and compaction test on its natural state. The expansiveness of the soil from the three locations were determined. The highest value of expansiveness from these samples considered for the experiment by the addition of waste materials concentration with 5%, 10% 20%, and 30% by weight. Test results indicated that the moisture content, free swelling, specific gravity Atterberg limit decreased, while the maximum dry density increased as the concentration of waste material increase. Hence, the minimum amount of waste materials comprised of 10% that will improve the strength of expansive clay soil for use in road subgrade construction.